Synthesis, bioactivities and cytogenotoxicity of animal fur-mediated silver nanoparticles. Issue 1 (March 2020) - Akintayo, G O; Lateef, A; Azeez, M A; Asafa, T B; Oladipo, I C; Badmus, J A; Ojo, S A; Elegbede, J A; Gueguim-Kana, E B; Beukes, L S; Yekeen, T A
Abstract: Animal waste materials are rarely used in the synthesis of nanoparticles compared to microorganisms and plant materials. The use of animal fur (goat) in synthesis could assist in turning waste to wealth. Thus, potentials of animal fur in the synthesis of silver nanoparticles (AF-AgNPs), its biological activities and safety through cytogenotoxicity were investigated. Animal fur (1 g) was hydrolyzed with 100 ml of 0.1 M NaOH at 90 ° C for 1 h, cooled and centrifuged at 4000 rpm for 30 min. The extract (1 ml) was added to 1 mM AgNO3 (40 ml) to reduce Ag + to its nanoparticles. The AF-AgNPs was characterized using UV–vis spectroscopy, Fourier-transform-infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and Energy Dispersive X-ray (EDX) analysis. Larvicidal, antioxidant, anticoagulant and thrombolytic potentials of AF-AgNPs were studied. Onion bulbs (20) were exposed to 0.01, 0.10, 1.0, 10.0 and 100.0 μg/ml of AF-AgNPs solution for its cytogenotoxicity study with AgNO3 solution and distilled water as controls. Microscopic (24, 48 and 72 h) assessment of the onion cells and macroscopic (72 h) evaluation of the roots were also studied. The AF-AgNPs solution was brownish with surface plasmon resonance at 419 nm. Evaluation of FTIR spectra showed that protein molecules were used as capping and stabilization agents. The AF-AgNPs had size range of 11.67-31.47 nm, caused 60-100% mortality of exposed Anopheles mosquito larvae in 12 h, and scavenged DPPH (40-59%) and hydrogen peroxide (75-94%). The nanoparticles also exhibited anticoagulant and thrombolytic potentials on human blood with 25% lysis compared to 13% observed for only extract. Various chromosomal aberrations and growth inhibition were induced by AF-AgNPs especially at 72 h of 100 μg/ml. Extract from animal fur was explored in biogenic synthesis of nanoparticles and found to have high potentials as antioxidant, anticoagulant, thrombolytic agents. Inhibition of cell growth observed especially at highest concentration can be explored in anticancer drugs though with caution due to AF-AgNPs potential to induce chromosomal aberrations.